Development of a web-based citizen contribution management system to optimize the financial management of community associations - Rizal, Fathur; Fani, Ubed Dwi; Sonda, Bima Tsaqif Syahhama; Hakam, Syaif; Urip, Muhammad; Fuadz Hasyim (Journal of Intelligent Decision Support System (IDSS), 2024)
This research aims to develop a web-based citizen contribution management system at D'Tar Residence to improve financial efficiency and transparency. Manual management of citizen contributions often causes transparency problems and delays in payment recapitulation. This research method uses the Waterfall system development model which includes the stages of needs analysis, system design, implementation, testing, distribution, and maintenance. Data collection was carried out through interviews, observations, and literature studies involving housing association administrators. This application was developed using the PHP programming language with the CodeIgniter framework and MySQL database. System testing was carried out using the Black Box Testing method to ensure that the application functions according to residents' needs. The results of the study indicate that the developed application can improve the efficiency of citizen contribution management and provide more transparent access to financial information. However, there are three features that require further refinement. Overall, this application is expected to encourage citizen participation in decision-making related to housing finances and increase satisfaction with the financial management of the association.